The Concept of Standard of Living and the Compilation of Its Indicators - Habibullayev Abrorjon Ahmadali’s son (Miasto Przyszłości, 2023)
The set of goods necessary for people’s life activities includes such diverse needs as working conditions, education, health, food and housing quality. The level of satisfaction of people’s needs depends on the level of individual and family income of society members. Living standards can be measured at the country level (for the entire population) and at the stratified micro level (for a specific group of the population). The first approach makes it possible to determine the standard of living of the population in different countries according to the gross domestic product per capita and make a comparative analysis.